The admissibility of polygraph test evidence in Malaysia / Ramalinggam Rajamanickam, Anita Abdul Rahim and Anisah Che Ngah - Rajamanickam, Ramalinggam; Abdul Rahim, Anita; Che Ngah, Anisah (Faculty of Administrative Science and Policy Studies, 2012)
In this technologically oriented society, detecting deception by examining bodily changes is not a new phenomenon. The test for examining the deception or lying is often referred to as a “lie detector test,” now referred to as polygraph test. Polygraph test evidence has been admitted as a relevant piece of evidence in some jurisdiction in the world. But, the position of polygraph evidence still remains ambiguous in the context of Malaysia Evidence Law. This paper, therefore, examines the relevancy of the polygraph evidence with regard to the Evidence Act 1950. The present paper focuses also on the issue of the admissibility of polygraph test evidence. The introduction of polygraph test is an important exemplar of the type of scientific issues that that courts must address.